1
x>0,y>0
{x²+y²=5
{log(2)x+log(2)y=1⇒log(2)xy=1⇒xy=2⇒2xy=4
прибавим
x²+y²+2xy=9
(x+y)²=9
a)x+y=-3
x=-3-y
-3y-y²=2
y²+3y+2=0
y1+y2=-3 U y1*y2=2
y1=-2 не удов усл
у2=-1 не удов усл
б)x+y=3
x=3-y
3y-y²=2
y²-3y+2=0
y1+y2=3 U y1*y2=1
y1=1⇒x1=2
y2=2⇒x2=1
(2;1);(1;2)
2
x>0,y>0
{x²-y²=12
log(2)x-log(2)y1⇒log(2)(x/y)=1⇒x/y=2⇒x=2y
4y²-y²=12
3y²=12
y²=4
y1=-2 не удов усл
y2=2⇒x=4
(4;2)
3
x>0,y>0
{x²+y²=25
lgx+lgy=lg12⇒xy=12⇒2xy=24
x²+y²+2xy=49
(x+y)²=49
a)x+y=-7
x=-y-7
-y²-7y=12
y²+7y+12=0
y1+y2=-7 U y1*y2=12
y1=-3 не удов усл
y2=-4 не удов усл
б)x+y=7
x=7-y
7y-y²=12
y²-7y+12=0
y1+y2=7 U y1*y2=12
y1=3⇒x1=4
y2=4⇒x2=3
(4;3);(3;4)
4
x>0 y>0
{log(0,5)xy=-1⇒xy=2
{x=3+2y
3y+2y²-2=0
D=9+16=25
y1=(-3-5)/4=-2 не удов усл
у2=(-3+5)/4=0,5⇒х=4
(4;0,5)
1. −(a+b)−(c−d)−(e−f)=−a-b−c+d−e+f
2. (8ab+3b)−(6ab−3b)+4a=8ab+3b−6ab+3b+4a=2ab+6b+4а
если a=6 и b=3. 2*6*3+6*3+4*6=36+18+24=78
3. 0,2x²+0,04y² +0,16x²−0,07y²=0,36x²-0,03y²
(0,2x²+0,04y²) -(0,16x²−0,07y²)=0,2x²+0,04y²-0,16x²+0,07y=0.11у²+0.04х²
4. (9a−13b+29c)−(−24a+29b−24c) =9a−13b+29c+24a-29b+24c=33а-42b+53с
5. (637d−214d²)+(114d²−137d)= 637d−214d²+114d²−137d=500d-100d²
6. 16−(7h+5)+4= 16−7h-5+4=15−7h
7. (x²−4x+3)−(3x−2x²+4)=x²−4x+3−3x+2x²-4=3х²-7х-1; если x=2.
3х²-7х-1=3*2²-7*2-1=12-14-1=-3
8. x³+3x²−x+4x³+2x²−x +5x²−3x³+4x =2x³+10x²+2х
9. это 42, т.к. 42-24=18